Grassroots Muslim women in religious conflict prevention in Tanzania: roles, contributions, and challenges - Japhet, Naisiligaki (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2022)
This paper analyzed how Muslim women at the grassroots level can prevent religious conflict in Tanzania by examining their roles, contributions, and challenges. This qualitative research used observation and in-depth interviews with the main respondents to address the three issues mentioned above. In contrast to their role and contributions to religious conflict prevention, the findings showed that Tanzanian Muslim women at the grassroots level faced numerous challenges. There are two major roles that grassroots Muslim women play in religious conflict prevention: raising awareness and providing religious education. Regarding their contributions, they supported and strengthened Islamic religiosity, empathy, and peace. Lastly, some of their challenges included a lack of resources and financial support, a lack of influence and participation, and a lack of expertise and skills in conflict prevention. The author recommends that other peacebuilding ventures can be studied, particularly by focusing on the contributions that have been played by upper and middle class Muslim women have played in reducing conflict within Muslim society.